The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/afe.12391
|View full text |Cite
|
Sign up to set email alerts
|

Wild bee (Apiformes) communities in contrasting habitats within agricultural and wooded landscapes: implications for conservation management

Abstract: 1 Semi-natural habitats are characterized by a high diversity of wildlife. However, other areas, e.g. old fields, can also play an important role in biodiversity conservation. 2 We assessed the species richness, abundance, and diversity of wild bees (Apiformes), including species of various functional groups in two contrasting and differently managed landscape types. For this study, we selected 15 xerothermic or sandy grasslands or extensively managed fresh meadows located in agricultural landscapes as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Many local and landscape factors can affect wild bee abundance and species richness in mid‐field woodlots. Significant factors include isolation (Steffan‐Dewenter & Tscharntke, 1999), habitat area (Steffan‐Dewenter, 2003), food resources (Alison et al, 2022; Kratschmer et al, 2019), and landscape heterogeneity (Jauker et al, 2009; Twerd & Sobieraj‐Betlińska, 2020). Generally, isolation combined with low landscape heterogeneity and small food resources can have a negative effect on the local abundance and species richness of bees.…”
Section: Introductionmentioning
confidence: 99%
“…Many local and landscape factors can affect wild bee abundance and species richness in mid‐field woodlots. Significant factors include isolation (Steffan‐Dewenter & Tscharntke, 1999), habitat area (Steffan‐Dewenter, 2003), food resources (Alison et al, 2022; Kratschmer et al, 2019), and landscape heterogeneity (Jauker et al, 2009; Twerd & Sobieraj‐Betlińska, 2020). Generally, isolation combined with low landscape heterogeneity and small food resources can have a negative effect on the local abundance and species richness of bees.…”
Section: Introductionmentioning
confidence: 99%
“…A decline in bee diversity will affect the pollination of many insect-pollinated crops and wild plant species. Although the honeybee (Apis mellifera L.) is generally regarded as the most important bee pollinator [25], wild bees are also relevant [22]. There has been growing concern about suspected declines in wild bee populations and the implications for agricultural and natural ecosystems [11].…”
Section: Introductionmentioning
confidence: 99%
“…Locally, species richness and abundance depend on plant species richness and cover as well as on the habitat composition and diversity in the surrounding landscape [9,22]. Furthermore, Schweiger et al [19] showed in an extensive sampling across Europe that wild bee communities are first influenced by the land use intensity in a region, then by the landscape structure, i.e., the proportion of semi-natural elements in the landscape.…”
Section: Introductionmentioning
confidence: 99%